Jim Crace Into the Wilderness (Springer International Publishing, 2018)
This is a unique essay collection on Jim Crace, locating his writing within contemporary philosophical, cultural and political debates. This timely first critical collection of essays on Crace's work provides a retrospective on his work to date, locating his work within a number of contemporary interdisciplinary critical and cultural perspectives and concerns, including post-humanism, post-millennial pastoralism, post-post feminism and gender, intersections between science and literary theory, environmental politics, the symbiotics of authorial and critical archival work, and the context of the burgeoning world of literary prizes. It includes additional contextual material in the form of an interview with Jim Crace and the re-publication of a seminal critical essay on "Craceland" by Adam Begley. As such this critical essay collection will be essential reading for anyone interested in contemporary fiction, and Crace's unique writing.